2013
DOI: 10.1001/jamapediatrics.2013.420
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Adverse Childhood Experiences Study Scale

Abstract: Our understanding of the most harmful childhood adversities is still incomplete because of complex interrelationships among them, but we know enough to proceed to interventional studies to determine whether prevention and remediation can improve long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
349
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(375 citation statements)
references
References 40 publications
16
349
2
8
Order By: Relevance
“…59 These experiences affect childhood health and well-being beyond any physical injuries incurred, leading to mental, physical, and behavioral problems. 28,60,61 Although not unexpected, given the negative impact of poverty on childhood physical health and emotional wellbeing, [62][63][64][65] the fact that economic hardship was so commonly cited as a stressor was significant nonetheless. These stressors involved witnessing parent financial struggles; and the lack of resources (ie, hunger, homelessness, and poor-quality clothing) caused by family financial struggles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 These experiences affect childhood health and well-being beyond any physical injuries incurred, leading to mental, physical, and behavioral problems. 28,60,61 Although not unexpected, given the negative impact of poverty on childhood physical health and emotional wellbeing, [62][63][64][65] the fact that economic hardship was so commonly cited as a stressor was significant nonetheless. These stressors involved witnessing parent financial struggles; and the lack of resources (ie, hunger, homelessness, and poor-quality clothing) caused by family financial struggles.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, researchers strengthened the association between ACEs and mental health symptoms by adding such measures to the ACE index and removing parental separation/divorce and incarceration of a household member. 28 Thus, the original index might be improved by considering a wider array of adverse experiences. More comprehensive childhood adversity measures exist but may not reflect inner-city youth experiences, as these measures were designed from interviews with mostly white, middle to upper middle class youth from rural and suburban communities.…”
mentioning
confidence: 99%
“…Other studies specifically focused on identifying ACEs in children in real time and reported that major childhood adversities, including growing up in poverty, peer rejection and lack of friends, poor school performance, property crime, and witnessing community violence, are associated with increased lifelong risk for negative life events and negative health outcomes as well. Measuring childhood adversities during childhood has been shown to offer improvements to the original ACE scale by examining more short-term behavioral and emotional symptoms that may serve as a link between ACEs and long-term health problems (8,9).…”
Section: Childhood Adversity: Definition and Scopementioning
confidence: 99%
“…Deliberately limited to household effects, ACEs exclude important factors taking place outside the home, such as bullying (Lereya et al, 2015) and racial discrimination (Slack et al, 2016). Researchers have therefore proposed amending the original ten measures to include a range of other harmful exposures, such as racism, witnessing community violence, living in an unsafe neighbourhood, bullying, a history of foster care, parental death, food scarcity, parents always arguing, peer rejection, low socioeconomic status, poor academic performance and having no good friends (Finkelhor et al, 2013;Wade et al, 2016). Extending the scope of ACEs in this way seems to provide a more accurate representation of the prevalence of adversity, especially for people living in deprived and ethnically diverse areas (Cronholm et al, 2015).…”
Section: Can Aces Help Us Understand These Effects?mentioning
confidence: 99%